Heurystyka strachu. Czy ambiwalencja lęku może być dla nas pouczająca? - Tibaldeo, Roberto Franzini (Uniwersytet im. A. Mickiewicza w Poznaniu Wydział Nauk Społecznych, Instytut Filozofii UAM, 2015)
The paper assumes that fear presents a certain degree of ambivalence. To say it with Hans Jonas (1903-1993), fear is not only a negative emotion, but may teach us something very important: we recognize what is relevant when we perceive that it is at stake. Under this respect, fear may be assumed as a guide to responsibility, a virtue that is becoming increasingly important, because of the role played by human technology in the current ecological crisis. Secondly, fear and responsibility concern both dimensions of human action: private-individual and publiccollective. What the ‘heuristics of fear’ teaches us, is to become aware of a deeper ambivalence, namely the one which characterizes as such human freedom, which may aim to good or bad, to self-preservation or self-destruction. Any public discussion concerning political or economic issues related with human action (at an individual or collective level) ought not to leave this essential idea out of consideration.
The Heuristics of Fear: Can the Ambivalence of Fear Teach Us Anything?
Keywords: Responsibility; heuristics of fear; technological risks; Hans Jonas